Evaluation of Pulmonary Tuberculosis Treatment in Adult Patients at Poly of Pulmonary Diseases Army Hospital Pematangsiantar City - Muharti Sanjaya; Dilla Sastia Mara; Almazhia Mahliza; Chika Ade Hendranti (International Journal of Public Health Excellence (IJPHE), 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is a health problem that still needs serious attention from the government and all levels of society because it can cause death. This study aims to determine the rationale for the treatment of pulmonary tuberculosis in adult patients at the Lung Disease Polyclinic at the Siantar City Army Hospital in 2021 which refers to the National Guidelines for Tuberculosis Management of the Indonesian Ministry of Health and treatment standards from WHO. This research is a non-experimental type with a descriptive evaluative design with retrospective data collection. The study was conducted using the medical records of adult pulmonary tuberculosis patients at the outpatient installation at the Pematang Siantar City Army Hospital in 2021. The results showed that the most common cases of pulmonary tuberculosis in adult patients were male patients, namely 61.22%, the diagnosis was for each patient suspected of pulmonary tuberculosis, a chest X-ray examination and smear test were carried out, pulmonary tuberculosis was treated using two anti-tuberculosis drugs, namely OAT-kombipak and OAT-FDC, 1 case was found with a duration of administration of anti-kombipak anti-tuberculosis drugs that did not comply with standard treatment and patients who received treatment received a score recovery of 97.96% and patients who failed treatment by 2.04%.